O Ensino a Distância: um reflexo da expansão mercantilizada da Educação Superior e os impactos no Serviço Social - Vidal, Karina Caputti (2016)
This dissertation has its object of study in the distance learning, which was introduced in the process of the higher education and its impacts in the Social Service. During this search, it was tried to acknowledge the following questions: Why are there distance education? How does it manifest? What are the results for the profession? From the understanding of the education as a social complex founded by the work, this analysis was given by bibliographic and documental search; with the proposal to learn the higher education, in the process of a capitalist way, and its relation with the work. The "contrarreforma" of education, from the incursion of the neoliberal process, in the decade of 1990 , in Brazil, brings an intense process of the higher education expansion; which was induced by programs and by actions of the latest governments and its limited relation with the internationals organisms. In this context the distance learning, manifests while the product of the process of a mass expansion of the higher education upon the market interests and the adaptation of a professional profile, adjustable with the capital's needs. Therefore, was identified that the formation/preparation of the social assistances suffers implications due to the unrestrained expansion of the college education, and with this bringing impact to Social service. Thus, throughout this study , was considered five pedagogic politics projects of the Higher education Institutions which represents a great number of educational poles in the state of Sao Paulo and also its importance to the educational market. The results shows that method of distance learning represents a significant expression in the formation of social assistances; it also reveals that the process of learning its further away from the formation supported by " Diretrizes Curriculares da ABEPSS" of 1996, and so this implying directly in the professional profile. The tendency is that, annually, the number of professionals that graduates in the distance education increase in relation of the students that attend a classroom; thus brings challenge to the profession and the definition of strategies that targeted the proximity of these professionals in the strengthening of the Project Ethic-Politic supported by the professional category